Long‐term outcome of primary immune‐mediated thrombocytopenia in dogs. (13th August 2018) - Simpson, K.; Chapman, P.; Klag, A.
Abstract : Objectives: To determine the incidence of relapse after discharge from the hospital in dogs with a diagnosis of presumed primary immune‐mediated thrombocytopenia, risk factors associated with relapse and whether or not indefinite use of immunosuppressive medication influences risk of relapse. Materials and Methods: Medical records from August 2007 through July 2016 were reviewed to identify dogs with a diagnosis of presumed primary immune‐mediated thrombocytopenia. Data collection included signalment, initial diagnostic tests, treatment, incidence of relapse, survival duration and follow‐up testing. Results: A total of 45 dogs were diagnosed, treated and monitored for at least one year for presumed primary immune‐mediated thrombocytopenia. 89∙6% of patients survived to discharge and 31% of those experienced a relapse following discharge. The median time from diagnosis to relapse was 79 days. Of dogs that experienced a relapse, 50% had at least one further relapse. There was no difference in age, body weight, gender, breed, platelet count at presentation, nadir packed cell volume during hospitalisation, incidence of melaena or initial treatment between the relapsing and non‐relapsing groups. In the relapsing group, time to platelet recovery was significantly longer and these patients were more likely to have received a blood transfusion. Clinical Significance: This study does not provide evidence to support the use of long‐term immunosuppressive medications to prevent relapse. However, the data suggest that patients with more severe disease at the time of diagnosis or that have already experienced a relapse should be monitored more closely.